«The Ukrainian language syllables book»: the dictionary of syllables by O. Riznykiv - Васильєва, Катерина Петрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The author of the article examines the dictionary of syllables by O. Riznykiv «The Ukrainian language syllables book» and determines the uniqueness of such a work, that has not been the object of special consideration yet. It is noted that O. Riznykiv, using the rules of syllabification was the first who made an attempt to collect, identify and systematize the most typical syllables characterized for the Ukrainian language. The number of them approaches approximately 9.600, and the dictionary covers 97-98% syllables from the Ukrainian literary language. It is emphasized that the author of the dictionary proposes to introduce into the science of linguistics the Ukrainian term «slovjak», which means a syllable or a set of syllables of a meaningful speech. In order to interest the readers, the dictionary by O. Riznykiv «The Ukrainian language syllables book» also contains the examples concerning «the mysterious nature of speeches», gives the linguists and theologians’ quotations and tries to reveal the links of speech with breathing. Due to the division of all syllables into the schemes, the article determines the number of different possible forms of syllables and its great diversity underlines the peculiarity of the Ukrainian language. It also defines the compatibility, the arrangement of vowels and consonants and justifies the allocation of a separate group of syllables that have only consonants.